2023
DOI: 10.1002/mnfr.202200671
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurrence of Mycotoxin‐Induced Hepatotoxicity in Mice Inhibited by Lycopene: Mitochondrial Impairment and Early Hepatic Fibrosis

Abstract: ScopeMycotoxins co‐contamination of agricultural products poses a serious threat to human and animal health, especially hepatic dysfunction. Zearalenone (ZEN), deoxynivalenol (DON), and aflatoxin B1 (AFB1) are three commonly co‐occurring mycotoxins. This study is to determine whether lycopene (LYC) can alleviate hepatic toxicity induced by the co‐occurrence of ZEN, DON, and AFB1 in mice.Methods and resultsEighty 6‐week‐old male ICR mice are divided into four groups: CON group (solvent control), LYC group (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These findings suggest that lycopene may protect against AFB1 toxicity by modulating the activities of CYP450 enzymes and phase II detoxification enzymes (see Figure 5). pretreatment with lycopene at a dose of 10 mg/kg per day through oral supplementation for 14 days markedly decreased the expression of hepatic CYP2E1 protein, consequently lowering AFB1-induced liver toxicity [150]. Moreover, Tang et al found that oral administration of lycopene at a dose of 100 mg/kg/day for 15 days significantly reduced the formation of AFB-DNA adducts in liver tissues, as well as the levels of AFM1, AFQ1, and AFP1 excreted in urine, along with AFB1-albumin adducts in serums of rats [49].…”
Section: Metabolic Interventionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings suggest that lycopene may protect against AFB1 toxicity by modulating the activities of CYP450 enzymes and phase II detoxification enzymes (see Figure 5). pretreatment with lycopene at a dose of 10 mg/kg per day through oral supplementation for 14 days markedly decreased the expression of hepatic CYP2E1 protein, consequently lowering AFB1-induced liver toxicity [150]. Moreover, Tang et al found that oral administration of lycopene at a dose of 100 mg/kg/day for 15 days significantly reduced the formation of AFB-DNA adducts in liver tissues, as well as the levels of AFM1, AFQ1, and AFP1 excreted in urine, along with AFB1-albumin adducts in serums of rats [49].…”
Section: Metabolic Interventionmentioning
confidence: 96%
“…Wan et al demonstrated that lycopene supplementation at a dose of 200 mg/kg in the basal diet for 42 days significantly decreased the activities of CYP1A1 and CYP2A6, albeit not affecting CYP1A2 and CYP3A4, thereby leading to a reduction in the formation of AFB1-DNA adducts and DNA damage in the liver tissues of chickens [64]. Lin et al observed that pretreatment with lycopene at a dose of 10 mg/kg per day through oral supplementation for 14 days markedly decreased the expression of hepatic CYP2E1 protein, consequently lowering AFB1-induced liver toxicity [150]. Moreover, Tang et al found that oral administration of lycopene at a dose of 100 mg/kg/day for 15 days significantly reduced the formation of AFB-DNA adducts in liver tissues, as well as the levels of AFM1, AFQ1, and AFP1 excreted in urine, along with AFB1-albumin adducts in serums of rats [49].…”
Section: Metabolic Interventionmentioning
confidence: 99%
“…Yu et al found that the administration of 5 mg/kg BW of lycopene to mice for 30 days significantly activated the NRF2/ARE signaling pathway, resulting in increased expression of downstream antioxidant genes and resistance against AFB 1 -induced kidney damage . In addition, lycopene alleviated hepatotoxicity, , mitochondrial damage, and ferroptosis in the jejunum, renal and cardiac damage, as well as erythrocyte dysfunction caused by AFB 1 through enhancing the overall antioxidant capacity of mice. Lycopene also attenuated AFB 1 -induced immunosuppression by inhibiting oxidative stress and mitochondria-mediated spleen apoptosis .…”
Section: Multiple Phytochemicals Against Afb1 Toxicitymentioning
confidence: 99%